Reconceptualizing International Student Mobility: A Multipolar Structure Lens - Xu , Xing (Journal of International Students, 2023)
This article examines shifting patterns in International Student Mobility (ISM), primarily the move from a South-North paradigm to a more multipolar structure. With emerging education hubs in South Korea, Malaysia, India, the Gulf States, and China challenging the West’s centrality, the study advocates a more nuanced approach to ISM research. It underscores the necessity of a geographical turn towards non-traditional areas and promotes a multipolar epistemology that privileges non-Western knowledge creation. The article also encourages investigation of sociocultural dynamics related to ISM, and suggests exploring underrepresented perspectives such as ethnicity, ecology, and gender in the post-pandemic world.